Non‐relativistic Eigen spectra with q‐deformed physical potentials by using the SUSY approach. (29th June 2016) - Eshghi, M.; Mehraban, H.; Ghafoori, M.
Abstract : The Schrödinger equation is solved for some of the q ‐deformed physical potentials within the framework of supersymmetric approach and supersymmetric Wentzel–Kramers–Brillouin approximation method. The energy levels are obtained with the corresponding normalized wave functions in terms of hypergeometric functions. The energy equations for some special cases of these potentials are discussed, and some of the thermodynamic quantities of the canonical system and the optical quantities of the two‐level system are calculated for one of the potentials. Some of the numerical results are shown, too. Copyright © 2016 John Wiley & Sons, Ltd.